Security of Electronic Payment Systems Based on Digital Money - A. B. Vavrenyuk; V. V. Makarov; V. S. Trofimova; I. V. Chugunkov (Безопасность информационных технологий, 2011)
Electronic payment systems based on digital money are evaluated in terms of information protection. Mechanisms of protection of interests of bank-emitter, buyer and seller are described. Course of life of a digital denomination is resulted: transactions of removal from the account, purchase and transfer into the account.